Late onset dominant cone dystrophy with early blue cone involvement. - Went, L N (1992)
A dominant cone dystrophy spanning seven generations was found in a pedigree from the Netherlands. The onset of the decline of visual acuity started after the age of 20, while a near complete absence of blue cone function (a so-called tritan defect) already existed before the presence of any ophthalmological abnormalities.